الشورى بين النص والتاريخ - عز الدين معميش (International Institute of Islamic Thought, 2016)
إن جوهر ما تقوم عليه الدولة في الإسلام هو الوظيفة العامة التي تحقق سيادةً ونظاماً للأمة يرعى المصالح الدينية والدنيوية. وتعدُّ مؤسسات الدولة وأجهزتها والنظام الذي يحكمها وسائط لتحقيق مقاصد شرعية، وعليه فإن أهمية الدولة وديمومتها واستقرارها أمور وثيقة الصلة بقدرتها على الوفاء بالمقاصد العامة للشريعة الإسلامية. والمبدأ الذي استقر عليه الجمهور هو أن ولاية الحكم في الإسلام إنما تقوم بالاختيار الحر أو الشورى، وأن الشورى يتجدد مفهومها وتتغير ممارستها تبعاً للظروف المختلفة على شرط تحقيق المقاصد التي حدَّدها الشارع الحكيم. تبحث هذه الدراسة في تجدد مفهوم الشورى عبر التاريخ انطلاقاً من النص الأصل، وتكشف عن مختلف النظريات والآراء التي استوعبها الفكر الإسلامي؛ نظراً وممارسةً في مراحل مختلفة من تاريخه، مبرزةً الجوانب الفريدة لمؤسسة الشورى التي تستحق منا أن نفاخر بها العالم. The essence of the state in Islam is to be a public office that maintains the sovereignty of the ummah and a system that takes care of religious and civic interests. The system and institutions of this state are means to attain purposes of Islamic law. The importance of the state, its durability and stability, are closely linked to its ability to fulfill these purposes. The established principle in Islam is to have a government through a free choice, or Shura. The concept of Shura is under continuous renewal and its practice varies depending on different conditions needed to achieve purposes set out by the Wise Legislator (Almighty God).This study examines the renewing concept of shura in history based on the original text, and reveals the various theories and practices of Islamic thought in different stages of its history, highlighting the unique system of Shura.